(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
In this article, it has been proven that τ-bounded spaces, if they satisfy the T2 (Hausdorff space) condition, are also T3 (Regular space) but not necessarily T4 (Normal space), with a counterexample provided. Additionally, the relationship between local weak density and local density has been examined.